Survival of non-oil producing monarchies from "Arab Spring": Morocco and Jordan - Bisharat, Zaineh (AUC Knowledge Fountain, 2014)
This thesis examines the survival of non-oil producing monarchies from the “Arab Spring”, by studying the historical context of Morocco and Jordan, the political and economic situations in the monarchies before and after the 2011 revolutionary wave and the transformation in mechanisms of control used by both regimes. The theoretical framework of this thesis rests upon dual causality, legitimacy and authoritarian upgrading. Legitimacy in this context refers to different types, be it traditional, religious or tribal, all which will be discussed in detail throughout the thesis. The concept of upgrading authoritarianism on the other hand is derived from Steven Heydemann’s work on transformation of authoritarian regimes in the Arab world. This thesis applies Heydemann’s five indicators of authoritarian upgrading on Morocco and Jordan through examining various reports including Freedom House, and Bertelsmann Stiftung. Research results are accumulated in the concluding chapter, where it becomes more evident that the latter causation does not completely apply to the non-oil producing Arab monarchies, as per Steven Heydemann’s indicators. However, alternative explanations of how Morocco and Jordan managed to evade the dire consequences of several neighboring “Arab Spring” republics is offered and supported.